Effectiveness of the Use of Exchange Rates and Loan Interest Charges Against Indonesian Non-Oil and Gas Exports - Francisca Sestri Goestjahjanti (Politeknik Negeri Semarang, 2020)
The purpose of this research is to analyze and discuss the effectiveness of Exchange rates and Loan interst expense used in partially and simultaneously on the value of Indonesia's Non -oil and gas exports from 1996 up to 2019. The analysis technique used in this study is linear regression, used SPSS software version 22. The research data collected during 24 years is time series secondary data. The explanatory research method in this research is to explain the relationship of one variable to other variables in a model, through the hypothesis test.This study concludes that found of model 1, has a partially significant effect, a positive of 43,90 %, between The exchange rate to Non-oil and Gas Exports. Model 2 has a partially significant effect, a negative of 79,60 %, between Loan interest expense on Non-Oil and Gas Exports. And model 3, there is a simultaneously significant effect of 81,30 %, a very strong relationship, between The exchange rate variable and Loan interest expense to the Indonesian Non-Oil and Gas Export variable.